The Colombian Section of The American College of Obstetricians and Gynecologists (ACOG) and voluntary recertification - Jimmy Castañeda (Federación Colombiana de Obstetricia y Ginecología, 2010)
The Colombian Federation of Associations of Obstetrics and Gynecology (La Federación Colombiana de Asociaciones de Obstetricia y Ginecología -FECOLSOG) has been working on establishing academic and scientific links with scientific and professional societies throughout the continent during the last few years to strengthen and diversify academic opportunities required by Colombian  gynaecologists, within Colombia and outside it.